Simulation and Forecast of Coastal Ecosystem Services in Jiaodong Peninsula Based on SSP-RCP Scenarios - Wenhui Guo; Ranghui Wang; Fanhui Meng (Remote Sensing)
This study simulated the spatiotemporal changes in coastal ecosystem services (ESs) in the Jiaodong Peninsula from 2000 to 2050 and analyzed the driving mechanisms of climate change and human activities with respect to ESs, aiming to provide policy recommendations that promote regional sustainable development. Future climate change and land use were forecast based on scenarios from the Coupled Model Intercomparison Project Phase 6 (CMIP6). The Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model was used to assess ESs such as water yield (WY), carbon storage (CS), soil retention (SR), and habitat quality (HQ). Key drivers of ESs were identified using Structural Equation Modeling (SEM). Results demonstrate the following: (1) High WY services are concentrated in coastal built-up areas, while high CS, HQ, and SR services are mainly found in the mountainous and hilly regions with extensive forests and grasslands. (2) By 2050, CS and HQ will show a gradual degradation trend, while the annual variations in WY and SR are closely related to precipitation. Among the different scenarios, the most severe ES degradation occurs under the SSP5-8.5 scenario, while the SSP1-2.6 scenario shows relatively less degradation. (3) SEM analysis indicates that urbanization leads to continuous declines in CS and HQ, with human activities and topographic factors controlling the spatial distribution of the four ESs. Climate factors can directly influence WY and SR, and their impact on ESs is stronger in scenarios with higher human activity intensity than in those with lower human activity intensity. (4) Considering the combined effects of human activities and climate change on ESs, we recommend that future development decisions be made to rationally control the intensity of human activities and give greater consideration to the impact of climate factors on ESs in the context of climate change.